(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article highlights the importance of character in human life. ​ It is shown that character accentuations are extreme expressions of the norm. ​ The negative influence of accentuations on the formation of personality is noted. ​ A theoretical analysis of literature on the subject of research was made. It is shown that the nature of the accentuation of the character is the same individual features, which tends to a potential transition to a certain pathological state.